Efficiency evaluation of grease traps prescribed by the Brazilian standard NBR 8160:1999 as natural flotation basins - Gnipper, Sérgio Frederico (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper evaluates Brazilian standard NBR 8160:1999 sized grease traps efficiency under natural flotation principles. Some characteristics of sanitary drainage systems effluent containing grease are presented, followed by ideal natural flotation horizontal basins sizing principles. Then, the application of those principles to grease traps is discussed, and the original efficiency removal evaluation criterion proposed by Fair et al. is presented and applied to the standard grease traps. The absence of a proper entrance chamber causes undesirable internal flow turbulence, delaying flotation action and reducing its efficiency. Standard small, single, and double grease traps in fact operate as mere siphon traps. It was concluded that empirical standard sizing criteria in force lead to remarkably low efficiency grease traps, which operate below the detention periods required for efficient adequate removal of grease particles. Standard sizing criteria should be revised, and adequate performance requirements should be established to allow grease traps to work as natural flotation basins.